Central Nervous System Myeloma and Unusual Extramedullary Localizations: Real Life Practical Guidance - Sammartano, Vincenzo; Cerase, Alfonso; Venanzi, Valentina; Mazzei, Maria Antonietta; Vangone, Beatrice Esposito; Gentili, Francesco; Chiarotti, Ivano; Bocchia, Monica; Gozzetti, Alessandro (Frontiers in Oncology, 2022)
Central nervous system localization of multiple myeloma (CNS-MM) accounts for about 1% of all MM during disease course or even rarer at diagnosis. A difference in the origin, i.e., osteodural or primary dural vs leptomeningeal/intraparenchymal, seems to define two distinct types of intracranial myeloma, with different clinical behavior. CNS-MM may occur also as a presentation of MM. Treatment is still unsatisfactory and many treatments have been reported: chemotherapy, intrathecal therapy, and radiotherapy, with dismal prognosis. Other sites of myeloma localization could be also of interest and deserve description. Because of the rarity and aggressiveness of the disease clinicians are often doubtful on how to treat it since there is no general agreement. Moreover, recent drugs such as the anti CD38 monoclonal antibody, immunomodulatory drugs, and proteasome inhibitors have changed the treatment of patients with MM with a significant improvement in overall response and survival. The role of novel agents in CNS MM management and unusual presentations will be discussed as well as the potential role of other new immunomodulatory drugs and proteasome inhibitors that seem to cross the blood-brain barrier. The purpose of this review is to increase awareness of the clinical unusual presentation and neuroradiological findings, give practical diagnostic advice and treatment options.